TL 18130 - Surgical treatment of hallux valgus using the modified Reverdin-Isham technique - Ribeiro Lara, Luiz Carlos; Lemos Rodrigues, Fábio; Grajales, Juan Antônio; Azevedo Torres Filho, Lucio Carlos (Scientific Journal of the Foot & Ankle, 2019)
Objective: The present study was conducted to clinically and radiographically analyze the outcomes of the surgical treatment of mild and moderate hallux valgus using the modified Reverdin-Isham technique. Methods: We retrospectively studied 46 feet of 39 patients with mild and moderate hallux valgus from June 2010 to July 2017. The mean postoperative follow-up was 36 months, and the mean patient age was 53 years. All patients who underwent the modified Reverdin-Isham technique were clinically and radiologically evaluated before and after surgery using the American Orthopedic Foot and Ankle Society (AOFAS) scale, and radiographs were acquired to calculate the hallux valgus angle (HVA), the intermetatarsal angle (IMA) and the distal metatarsal articular angle (DMAA). Results: The AOFAS score increased by a mean of 54 points. Radiologically, the mean HVA decreased by an average of 17.1°, the IMA by 4.2° and the DMAA by 12°. Conclusion: The modified percutaneous Reverdim-Isham technique made it possible to correct mild and moderate hallux valgus deformities with good angular correction and increased stability compared with the classical technique, in addition to providing an increase in the AOFAS score.